[Car]nival: empowering Lenasia's informal 'motor-tainment' industry - Mistry, Rajiv (My University, 2015)
This thesis is part fantasy, part real and part ironic. The automobile enthusiast market has evolved into a fully-fledged entertainment industry where driving is a mere portion of the car experience. With a rich cultural, social, political, spatial, and economic presence in South Africa, it is clear that this informal culture has a religion and following all to its self. Reflecting this, Lenasia, located south of Johannesburg (a predominately Indian township as a result of the apartheid regime) has become notorious for modified cars, loud music and raging petrol-heads. With minimal infrastructure in and around the urban footprint to support this growing culture, car enthusiasts have no option but to take to the streets of the residential suburbs to flaunt their glistening cars and test their roaring engines. This in turn has become a conflicting issue between some frustrated community members and passionate car enthusiasts. More importantly, it has also become a life threatening predicament which has claimed several lives within the community thus far. This recurring conflict has emerged as the vital point of enquiry for this thesis. Addressing the concerns with which this stimulating yet life threatening culture is synonymous, the location of the site plays a vital role in this proposal. The chosen site, Albert Street, is located on the edge of the township. It has a history of being drag raced on and is embedded in an established and robust industrial district which hosts a range of depleted automobile and other workshops which build, “pimp” and recycle cars. This intriguing juxtaposition of construction, de-construction and transformation has proven to be a suitable theme with which to engage in terms of appropriating the anatomy of the street arena and associated fabric into a celebrated “motor-tainment” utopia by night and after hours, but also preserving the current industrial networks of production, retail and repairs by day and during working hours. It will boast programmes amongst others: an appropriated drag racing strip, a multi-purpose activity capsule, a customisation and training facility, various “rent a workshop” spaces and safe spectatorship areas with medical, security and various other support facilities.
This document is submitted in partial fulfilment for the degree: Masters of Architecture (Professional) University of the Witwatersrand, Johannesburg, South Africa, 2014
Keywords: City planning; South Africa, Johannesburg; Motor vehicles; Public spaces; Lenasia; Automobiles